Ethics in organizations: A framework for theory and research - Nicholson, Nigel (Journal of business ethics, 1994)
In a climate of increasing interest and activity within the field of business ethics, as yet there exists no coherent conceptual framework for organizational theory and research. From a review of current thinking and previous writings a framework of concepts is suggested to help set an agenda for empirical research. The elements of this are, first, a taxonomy of “ethical domains”: the foci of organizations' and their agents' ethical concerns and conduct. Second, it is considered how “ethical functioning” might be analysed in terms of causal relationships between expressive forms, voluntary action and instituted forms. Third is discussed “ethical process”, the means by which ethical awareness is aroused. Fourth and last, the paper examines how normative evaluations might apply to the “ethical condition” of organizations and their agents, meaning change or stability in reputation and integrity. At each stage of the argument possible objectives for research are developed.